(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Psacothea hilaris (Pascoe) is recorded for the first time in Europe. The species was found in 2005 in Lombardy (Italy). It is a xylophagous coming from Asia. It attacks plants from the family of Moracae. Informations about distribution, biology and control are reported.